Sistem Informasi Desa Pagarjati Kabupaten Lahat Berbasis Website - Deni Erlansyah; Ranti Yusnita (LPPM STIKOM Tunas Bangsa, 2024)
Technological developments have occurred so rapidly and have encouraged various innovations in the field of information and communication technology, which have changed the way people interact and obtain information. Website-based information systems in villages have an important role in supporting transparency and easy access to information, as well as opening up new economic opportunities by promoting agricultural products. Pagarjati Village still uses manual methods to share information, by attaching it to the notice board in the village hall, and Pagarjati Village also does not have information media to introduce and promote the activities and agricultural products of Pagarjati Village. The method used in this research is Rational Unified Process (RUP), this research was conducted in Pagarjati village, Lahat Regency. The aim of this research is to design and build a website-based information system in Pagarjati village and introduce and promote the activities and agricultural products of Pagarjati village. The existence of this information system helps Pagarjati village officials to support transparency and ease of information, as well as efforts to improve the economy by promoting agricultural products from Pagarjati village